Dynamics Finite Element for Ship Damage Collision Analysis - Hasanudin Hasanudin; Wasis Dwi Aryawan; Achamd Zubaydi; Teguh Putranto (IPTEK Journal of Proceedings Series, 2017)
Abstract¾ Along with the growing fleet of vessels, ship collision accident cases are becoming more frequent. It is unavoidable that the rapid shipping due to the number of vessels that operate relatively large and the ship is waiting for the loading and unloading at the port. This study will examine the design of the solid bulk cargo ship safe for shipping operations congested areas. The finite element method is used to determine the amount of internal energy in the structure of damaged vessel. The striking ship is assumed a tanker that have a bulbous bow. Bulk carrier is designed with space of double skin 1.8 m and the structure of wing tank is determined previously. The results obtained from this research is the design of the cargo hold of bulk carrier that has a double skin to protect the leaking compartment when the ship was crashed. Penetration in depth 1.8 m will be occurred at ship if ship crashed is with speed 12 knots and weight 1400 tons.